2011
DOI: 10.1002/jnr.22644
|View full text |Cite
|
Sign up to set email alerts
|

Activation and modulation of human α4β2 nicotinic acetylcholine receptors by the neonicotinoids clothianidin and imidacloprid

Abstract: Neonicotinoids are synthetic, nicotine-derived insecticides used for agricultural and household pest control. While highly effective at activating insect nicotinic receptors, many neonicotinoids are also capable of directly activating and/or modulating the activation of vertebrate nicotinic receptors. In this study, we have investigated the actions of the neonicotinoids clothianidin (CTD) and imidacloprid (IMI) on human neuronal α4β2 nicotinic acetylcholine receptors. The data demonstrate that the compounds ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 28 publications
2
60
0
Order By: Relevance
“…It has been reported (Bray et al, 2005) that sperm nAChRs play a central role in the control of motility associated with calcium influx mechanisms, and mice deficient in the nAChR subunit, a7, produce impaired sperm motility. Li et al (2011) have also reported that imidacloprid, but not CTD, strongly inhibits the a4 and b2 subunits of nAChRs activated by acetylcholine in human embryonic kidney cells. Therefore, any drug-affected nicotinic system may cause disturbed function of testicular tissue and sperm.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported (Bray et al, 2005) that sperm nAChRs play a central role in the control of motility associated with calcium influx mechanisms, and mice deficient in the nAChR subunit, a7, produce impaired sperm motility. Li et al (2011) have also reported that imidacloprid, but not CTD, strongly inhibits the a4 and b2 subunits of nAChRs activated by acetylcholine in human embryonic kidney cells. Therefore, any drug-affected nicotinic system may cause disturbed function of testicular tissue and sperm.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported (Bray et al 2005) that sperm nAChRs play a central role in the control of motility associated with the calcium influx mechanisms, and mice deficient in nAChR subunit α7 produce impaired sperm motility. Li et al (2011) have also reported that although neonicotinoids imidacloprid but not CTD strongly inhibits the α4 and β2 subunits of nAChR activated by acetylcholine in human embryonic kidney cells. Therefore, any drug affected nicotinic system may cause disturbed function of the testicular tissue and sperm.…”
Section: Discussionmentioning
confidence: 93%
“…Neonicotinoids are not only used for agricultural crop protecNeonicotinoids are broad-spectrum insecticides, acting on nicotinic acetylcholine receptors providing a selecnicotinic acetylcholine receptors compared to the vertebrate equivalents (Matsuda et al, 2001;Bal et al, 2010;Li et al, 2011). Previously the correlation between nicand improved insulin sensitivity was reported (Xu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%